Risk Factors for Sudden Infant Death in North Carolina - Yamada, Merick M.; Rosamilia, Michael B.; Chiswell, Karen E.; D'Ottavio, Alfred; Spears, Tracy; Osgood, Claire; Miranda, Marie Lynn; Forestieri, Nina; Li, Jennifer S.; Landstrom, Andrew P. (Frontiers in Pediatrics, 2021)
Background: Sudden infant death syndrome (SIDS) is the sudden, unexplained death of infants less than one year old. SIDS remains a leading cause of death in US infants. We aim to identify associations between SIDS and race/ethnicity, birth weight/gestational age, and socioeconomic/environmental factors in North Carolina (NC) to help identify infants at risk for SIDS. Methods and Results: In this IRB-approved study, infant mortality 2007-2016 and death certificate-linked natality 2007-2014 were obtained from the NC Department of Health and Human Services. General, NC natality statistics 2007-2016 were obtained from CDC Wonder. Association between SIDS/total infant death and covariates (below) were calculated. Total infant mortality decreased 2007-2016 by an average of 14 deaths/100,000 live births per year, while SIDS incidence remained constant. Risk ratios of SIDS/total infant deaths, standardized to Non-Hispanic White, were 1.76/2.41 for Non-Hispanic Black and 0.49/0.97 for Hispanic infants. Increased SIDS risk was significantly and independently associated with male infant sex, Non-Hispanic Black maternal race/ethnicity, young maternal age, low prenatal care, gestational age <39 weeks, birthweight <2500g, low maternal education, and maternal tobacco use (p<0.01). Maternal previous children now deceased also trended toward association with increased SIDS risk.